Cost-effective genotyping of human MBL2 gene mutations using multiplex PCR - Skalníková, Helena; Freiberger, Tomás; Chumchalová, Jitka; Grombiríková, Hana; Sedivá, Anna (Journal of immunological methods, 2004)
Mannose-binding lectin (MBL) deficiency is associated with increased susceptibility to various infections and autoimmune disorders. It is caused by certain polymorphisms in the MBL2 gene promoter and mutations in the coding region of the gene. In this report, we present a novel, rapid, efficient and cost-effective method of two multiplex polymerase chain reactions (PCRs) for the assessment of three structural point mutations within exon 1 at codons 52, 54 and 57. Three additional PCR reactions for the detection of promoter polymorphisms at positions -550 and -221 were performed. MBL2 haplotypes in 359 individuals of the general Czech population were detected using this approach. The rare LYD haplotype was found in 1.1% of all alleles.
Keywords: Molecular Sequence Data; analýza nákladů a výnosů; sekvence aminokyselin; genotyp; Genotype; polymerázová řetězová reakce; Czechoslovakia; Mannose-Binding Lectin; Polymerase Chain Reaction; Promoter Regions, Genetic; Československo; mutace; Cost-Benefit Analysis; fenotyp; Phenotype; Mutation; Humans; Amino Acid Sequence; promotorové oblasti (genetika); molekulární sekvence - údaje; lidé; lektin vázající mannosu